Sifat Fisiko-Kimia Dendeng Daging Giling terkait Cara Pencucian (Leaching) dan Jenis Daging yang Berbeda - . Suharyanto; R Priyanto; E Gurnadi (Faculty of Animal Science, Bogor Agricultural University, 2008)
Dendeng is a typical Indonesian jerked meat commonly made from sliced or ground beef with 2 mm thickness. This research was conducted to study the effect of kind of meat and leaching method on pH, toughness, protein, fat content and peroxide value (PV) of ground jerked meat. The experiment was set up in a completely randomized factorial design with three replications. The first factor was three levels of leaching methods (no washing, washed in 1.5 x 1.5 x1.5 cm size and washed minced meat). The second factor was kind of meat namely horse meat, lamb and beef. The results indicated that neither interaction effect between leaching and kind of meat nor effect of leaching were significant on all characteristics observed. Kind of meat influenced significantly on the pH, toughness, fat content and PV of dendeng (P < 0.01). Key words: dendeng, physical-chemical characteristics, leaching